Assessment of Acute Kidney Injury in Patients Undergoing Elective Coronary Angiography and Percutaneous Coronary Intervention - Alam, ABMM; Moniruzzaman, M; Alam, MB; Islam, N; Khatoon, F; Jahan, N; Ali, Z; Chowdhury, NU (Cardiovascular Journal, 2012)
Background: CIN has gained increased attention in the clinical setting, particularly during cardiac intervention but also in many other radiological procedures in which iodinated contrast media are used. There is at present good clinical evidence from well-controlled randomized studies that CIN is a common cause of acute renal dysfunction. Methodology: This was a prospective study conducted among the patients who underwent coronary angiography and percutaneous coronary intervention in the Department of Cardiology, Dhaka Medical College Hospital during January 2010 to December 2010. A total of 111 patients age range from 25 to 75 years were included in the study. Serum creatinine level at baseline and at the end of 48 hours was done in all these patients. Study population was divided into two groups according to development of acute kidney injury (AKI). Group-I = AKI, Group II = Not developed AKI. Results: AKI developed 11.7% of the study patient. DM and Preexisting renal insufficiency were significantly higher in group I patients. HTN was (61.5% Vs 44.9%) higher in group I but not significantly. History of ACE inhibitor/ARB, NSAID intake and LVEF <40% were significantly higher in group I patients. The mean±SD volume of CM (Contrast Media) were 156.9±44.8 ml and 115.4±30.0 ml in group I and group II respectively, which was significant. The mean±SD of serum creatinine after 48-72 hours of CAG/PCI was 1.4±0.37 mg/dl and 1.1±0.2 mg/dl in group I and group II respectively. The serum creatinine level increased significantly (p<0.05) after 48-72 hours of CAG/PCI in group I. In group II, S. creatinine level increased but not significant (p>0.05). Impaired renal function was found 76.9% and 2.0% in group I and group II respectively. DM, HTN, preexisting renal insufficiency, ACE inhibitor/ARB, NSAIDs, contrast volume (>150 ml), eGFR (<60 ml/min/ 1.73m2) and LVEF (<40%) are significantly (p0.05) associated for CIN development. Conclusion: CIN is an iatrogenic but preventable disorder results from the administration of contract media. Although rare in the general population, CIN occurs frequently in patients with underlying renal dysfunction and diabetes. In patients with pre angiographic normal renal function, the prevalence is low but in pre-existing renal impairment it may pose a serious threat. Thus risk factors are synergistic in their ability to predispose to the development of CIN. A careful risk-benefit analysis must always be performed prior to the administration of contrast media to patients at risk for CIN. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12227 Cardiovasc. j. 2012; 5(1): 37-43